Penerapan Model Pembelajaran Cooperative Learning Tipe Talking Stick untuk Meningkatkan Aktivitas Siswa dalam Pembelajaran Tematik (PTK Pada Siswa Kelas IV D SD 71 Kota Bengkulu) - mustika, fitri indah; swistoro, Eko (TRIADIK, 2017)
ABSTRACTThe thematic learning process that took place in grade IV D SD Negeri 71 Kota Bengkulu was less attractive and not in accordance with the characteristics of students who liked the game. This can be seen from the lack of enthuasiasm of students inlearning. This research aims to determine the increase of students activities in thematic learning after applying the cooperative learning model of talking stick in grade IV D students in the second semester of the 2017/2018 school year in SD Negeri 71 Kota Bengkulu with research subjects namely fourth grade students of SD Negeri 71 Kota Bengkulu totaling 26 students. This research was carried out in two cycles. Data collection techniques in this study were carried out using observastion sheets. The analysis used is descriptive analysis. The results of observing the acttivities of students in cycle I to cycle II showed an increase of 9.0 from 3,73 to 46,3 in category of being quite good.Key words : Talking stick learning model, student activity